2015
DOI: 10.1017/s0950268815001302
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis A in Iranian adolescents: is it time to introduce a vaccine?

Abstract: Universal vaccination of children for hepatitis A virus (HAV) has emerged as a cost-effective strategy to prevent this infection in regions with high incidence of symptomatic disease. Age-specific seroprevalence surveys are practical and reliable methods to estimate the rate of susceptibility in populations, and to help the implementation of vaccination policies. We surveyed the age-specific HAV seroprevalence in a nationally representative sample of Iranian adolescent students aged 10-18 years. Serum samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
2
13
1
Order By: Relevance
“…As previously reported, the overall rate of HAV seropositivity in Iran is 64%, which increases sharply from 14.8% at age 10 to 72.9% at age 13 (3). Iran is a vast country consisting of 31 provinces with differing sanitary conditions and socioeconomic properties, so the prevalence of this infection is expected to vary across various parts of the country.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…As previously reported, the overall rate of HAV seropositivity in Iran is 64%, which increases sharply from 14.8% at age 10 to 72.9% at age 13 (3). Iran is a vast country consisting of 31 provinces with differing sanitary conditions and socioeconomic properties, so the prevalence of this infection is expected to vary across various parts of the country.…”
Section: Introductionsupporting
confidence: 61%
“…Previously, we reported that HAV seropositivity was not related to gender or to residence area (urban/rural), and that seropositivity increased with age (3). This study investigated the household- and provincial-level risk factors for HAV.…”
Section: Discussionmentioning
confidence: 83%
“…This view is further supported by the IgG prevalence being the lowest in the age group 10-14 years which is not covered by the HAV immunisation schedule by the Ministry. Some studies have shown that two doses of HAV vaccine administered to children would lead to a significant decrease in acute HAV incidence in all age groups [24]. In addition, the HAV immunity rate, which increases with increasing age, leads to a decrease in anti-HAV IgM positivity rates in older age groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that there is a declining trend in terms of immunity level against hepatitis A in Iranian children and a gradual shift for occurrence of HAV infection in adulthood that urge active immunization via vaccination against this virus (25). Currently, vaccination against HAV is not included in the national immunization program of Iran (26), however, given the high seroconversion rate of HAV among Iranian adolescents, extensive vaccination of children seems reasonable (27).…”
Section: Discussionmentioning
confidence: 99%